Effectiveness of Mini Shadow Puppet Media Storytelling Model to Develop Speaking Competence of Fifth-Grade Elementary School Student - ZULFAN, IQBAL; Zainuddin, Almuntaqo (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Speaking is one of the language skills that must be mastered by every student, because speaking is a means of expressing ideas. In fact, speaking competence is given less attention by teachers in the learning process. The low speaking competence of elementary school students can be seen from several studies such as at SDN 36 Pontianak Kota, only 26% of 30 students have speaking competence in the good category, and SDN S4 Bandung, only 1% of SDN S4 Bandung students are said to be quite capable of retelling the fairy tales they have heard using their own words. This study aims to develop Mini Shadow Puppet learning media with Storytelling model to improve the speaking competence of elementary school students. This research uses the R&D (Research & Development) development method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The trial of learning media was conducted to 20 students of SD Muhammadiyah 1 Surakarta. The results of this research show that Mini Shadow Puppet media is valid and feasible to use, this is based on four validation results, namely media expert validation obtained at 75%, material expert validation obtained at 78%, and trials using media that show an increase in speaking competence by 9%. The results of the user questionnaire filled in by students obtained a value of 92.5% in the acceptable category. This shows that the solution using Mini Shadow Puppet media is effective for students.